2021
DOI: 10.1002/1873-3468.14200
|View full text |Cite
|
Sign up to set email alerts
|

MEK/ERK MAP kinase limits poly I:C‐induced antiviral gene expression in RAW264.7 macrophages by reducing interferon‐beta expression

Abstract: Toll-like receptor 3 (TLR3) recognizes viral double-stranded RNA (or the synthetic dsRNA analog poly I:C) and induces a signal transduction pathway that results in activation of transcription factors that induce expression of antiviral genes including type I interferon (IFN-I). Secreted IFN-I positively feeds back to amplify antiviral gene expression. In this report, we study the role of MEK/ERK MAP kinase in modulating antiviral gene expression downstream of TLR3. We find MEK/ERK is a negative regulator of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In IRF3 −/− macrophages, poly I:C failed to stimulate NO production [ 42 ]. Mechanistic experiments allowed authors to suggest that ERK and IRF3 coordinate induction of NO by macrophages in response to stimulation of TLR3 [ 43 ]. These data support our observations on the critical role of IRF3 in the induction of crucial macrophage polarization markers.…”
Section: Discussionmentioning
confidence: 99%
“…In IRF3 −/− macrophages, poly I:C failed to stimulate NO production [ 42 ]. Mechanistic experiments allowed authors to suggest that ERK and IRF3 coordinate induction of NO by macrophages in response to stimulation of TLR3 [ 43 ]. These data support our observations on the critical role of IRF3 in the induction of crucial macrophage polarization markers.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to mock-treated cells, a markedly impaired production of JEV viral RNA and E protein, as well as viral particles in U0126, was observed, but this change was not noticed in 17-AAG-treated hBMECs (Figures 6F-H). Previous reports have demonstrated that ERK negatively regulates the interferon signaling-mediated antiviral response (Yang and Ding, 2019;Freed et al, 2021). Therefore, the expression of interferons and ISGs was also measured with U0126 treatment in JEV-infected hBMECs.…”
Section: Erk Is Downstream Of Egfr In Regulating Interferon Signaling...mentioning
confidence: 99%